THE RELATIONSHIPS BETWEEN RENAL RESISTIVE INDEX AND CORONARY RISK FACTORS AND CORONARY HEART DISEASE. (June 2018) - Higuchi, Y.; Kagiyama, S.; Maebuchi, D.; Oniki, H.; Naka, Y.; Nyuta, E.; Ohishi, T.; Seki, T.
Abstract : Objective: Renal resistive index (rRI) can be measured in renal vascular echography and is reported to be associated with renal parenchymal damage. However, little is known about its clinical importance. In the present study, we investigated the relationships between rRI and coronary risk factors in the patients who were suspected or suffered from coronary heart disease (CAD) and stroke. Design and method: We enrolled the patients who underwent renal vascular echography from September 2014 to August 2017, and excluded the patients with severe chronic kidney disease (estimated glomerular filtration rate (eGFR) < 15). The XarioXG (Toshiba Medical Systems, Tochigi, Japan) ultrasound device and a 3.5-MHz probe were used to obtain images for RI measurement. The rRI was defined as (peak systolic velocity - end diastolic velocity) / peak systolic velocity. In each patient, rRI at the interlobular was measured in the middle portions of the kidney in a supine position and was averaged for each kidney. The mean rRI value of both kidneys was used for analysis. We also examined the association with intima media thickness (IMT) of carotid artery, pulse wave velocity (PWV), and underlying clinical features and parameters. Results: The number of patients was 331 (male/female = 225/106), and the mean age was 66.4 years old. The rRI was significantly increased with age, serum creatinine and decreased with eGFR. The patient with hyperlipidemia (n = 204, p < 0.05), hypertension (n = 276, p < 0.01), diabetes mellitus (n = 81, p < 0.01), CAD (n = 125, p < 0.01) or stroke (n = 70, p = 0.01) showed significantly higher rRI than the patients without these diseases. Disease severity of CAD assessed by the number of diseased vessels significantly associated with the rRI. (p = 0.02). Especially, the patients with three vessel diseases showed significantly higher rRI than the patients without coronary disease or with single/double vessel diseases (p < 0.01). Furthermore, the rRI significantly associated with IMT (p = 0.02) but not with PWV (p = 0.74). Conclusions: In the present study, we found that the rRI significantly associated with not only clinical feature and parameters but also IMT. These results revealed that the rRI had close relationships with coronary risk factors.